Detection of polyamines by an enzymatic assay. (6). Fundamental and clinical studies of a simple enzymatic method for determining total polyamines in blood - Koide, T (Hinyokika kiyo. Acta urologica Japonica, 1987)
A simple enzymatic method for determining total polyamines in human blood was established. Polyamines in trichloroacetic acid extract from 1 ml of blood were isolated on an anion-exchange column and measured spectrophotometrically by the end point assay using polyamine oxidase and putrescine oxidase. The recovery was as high as 98.4% and within-run precision (coefficient of variance: 1.82%), and the values obtained by this method were in fair agreement with those obtained by high performance liquid chromatography and the enzymatic differential assay methods previously reported. The polyamine levels were not changed when the blood was stored at -20 degrees C. Blood polyamine levels were measured in 108 patients with genitourinary cancers, 29 patients with benign prostatic hypertrophy, 18 patients with benign urological diseases and 25 normal subjects. Although polyamines were not significantly elevated in the low stage of cancer, elevation was observed at a high stage of malignancy. These results indicate that the determination of total polyamines may be useful to determine biochemically the malignancy of cancers